2012
DOI: 10.1002/esp.3201
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of suspended sediment sources in an alpine catchment combining river/rainfall monitoring and sediment fingerprinting

Abstract: Influence of the rainfall regime on erosion and transfer of suspended sediment in a 905‐km² mountainous catchment of the southern French Alps was investigated by combining sediment monitoring, rainfall data, and sediment fingerprinting (based on geochemistry and radionuclide concentrations). Suspended sediment yields were monitored between October 2007 and December 2009 in four subcatchments (22–713 km²). Automatic sediment sampling was triggered during floods to trace the sediment origin in the catchment. Sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 47 publications
2
80
1
1
Order By: Relevance
“…On the other hand, event-based sampling also has important advantages in that they contain information on variation in sediment sources over time, both within and between events (Collins et al, 2001;Minella et al, 2008). This is especially true for small drainage basins, where sediment is emitted within events and there is interest in knowing how the emission of sediment varies within and between events (Collins et al, 2001;Minella et al, 2008;Navratil et al, 2012). In such catchments, it may be important to define the minimum number of samples needed to describe variability of the process adequately, whilst optimizing monitoring and laboratory costs.…”
Section: Sampling and Laboratory Analysis In Fingerprintingmentioning
confidence: 97%
“…On the other hand, event-based sampling also has important advantages in that they contain information on variation in sediment sources over time, both within and between events (Collins et al, 2001;Minella et al, 2008). This is especially true for small drainage basins, where sediment is emitted within events and there is interest in knowing how the emission of sediment varies within and between events (Collins et al, 2001;Minella et al, 2008;Navratil et al, 2012). In such catchments, it may be important to define the minimum number of samples needed to describe variability of the process adequately, whilst optimizing monitoring and laboratory costs.…”
Section: Sampling and Laboratory Analysis In Fingerprintingmentioning
confidence: 97%
“…These range from seasonal variations in SPM concentration driven by changing antecedent soil moisture conditions (Meybeck et al 1999;Halliday et al 2014) to hourly fluctuations driven by episodic high-energy, high-flow storm events which can mobilise large volumes of material through the initiation of rapid land-to-river surface sediment transfers (Navratil et al 2012;Cooper et al 2015). Intriguingly, recent research in North America and Europe has also found evidence of distinct diel cycles in fluvial SPM concentrations (Gillain 2005;Loperfido et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…At least five devices were available at the same time from 15 November 2011 (see Table A2 in Appendix A for the period of operation of the instruments). Moreover, a 2-D video disdrometer (2-D VD) was deployed at Le Pradel (south of the Gazel catchment) in autumn 2012 and 2013 for an inter-comparison of measurements (Raupach and Berne, 2015). All Parsivels except Saint-Etienne de Fontbellon and Pradel-Grainage are colocated with rain gauges from the network described in the next paragraph (Fig.…”
Section: Disdrometersmentioning
confidence: 99%
“…4). The correction technique described by Raupach and Berne (2015) using the 2-D VD as a reference disdrometer has been applied to Parsivel data, improving the consistency of recorded drop size distribution (DSD) moments.…”
Section: Disdrometersmentioning
confidence: 99%
See 1 more Smart Citation